2017
DOI: 10.1002/ejp.996
|View full text |Cite
|
Sign up to set email alerts
|

Is this back pain killing me? All‐cause and cardiovascular‐specific mortality in older Danish twins with spinal pain

Abstract: Older people reporting spinal pain have 13% increased risk of mortality per year lived. However, this association is not likely to be causal, with the relevant confounders contributing to this relationship. Thus, pain in the spine may be part of a pattern of poor health, which increases mortality risk in the older population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…First, our study compared those with the same injury, differing only in whether or not they experienced disability from that injury. Nevertheless, our results could be influenced by several confounders, which we are not able to control for in our study, such as smoking, obesity, and depression which are risk factors for disability and increase mortality from specific causes such as cancer, heart disease, and intentional self‐harm . On the other hand, the follow‐up period of our study occurred during a time of increased physician prescribing of opioids and the predictors of disability from low back pain have been found to be predominantly psychosocial variables and not perceived health status .…”
Section: Discussionmentioning
confidence: 64%
“…First, our study compared those with the same injury, differing only in whether or not they experienced disability from that injury. Nevertheless, our results could be influenced by several confounders, which we are not able to control for in our study, such as smoking, obesity, and depression which are risk factors for disability and increase mortality from specific causes such as cancer, heart disease, and intentional self‐harm . On the other hand, the follow‐up period of our study occurred during a time of increased physician prescribing of opioids and the predictors of disability from low back pain have been found to be predominantly psychosocial variables and not perceived health status .…”
Section: Discussionmentioning
confidence: 64%
“…This work extends research on disabling back pain and increased mortality. 13,14 To our knowledge, our study is the first to measure disability after measurement of back pain, allowing prospective analysis of disability as a mediator of the association between back pain with mortality. Using causal mediation methods that incorporate interaction between exposure and mediator variables, 24,25 self-reported IADL impairment was an important mediator of this association.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] Two studies separated back pain into multiple phenotypes based on pain frequency or impact on physical function, both found an elevated risk of mortality among older women. 14,15 Other studies dichotomized back pain exposure; of these, two observed a small increase in mortality among older adults but did not provide sex-specific results, 13,16 and five found no association. [8][9][10][11][12] All previous studies measured back pain at a single time point.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Evidence also shows an association between LBP and increased risk of mortality in older adults per year lived, although the association does not seems to be causal. 13 Furthermore, compared with pain-free individuals, older adults with LBP have more psychosocial dysfunction, self-reported disability, and physical performance impairments, 14 that may contribute to a worse trajectory of the symptoms. 15 As life expectancy increases, 16 the number of older adults with back complaints tends to be higher, contributing for more years living with disabilities.…”
mentioning
confidence: 99%